Aplikasi Teori Model Colcaba Dalam Pemenuhan Kebutuhan Rasa Nyaman Pada Neonatus Dengan Atresia Duodenum - Nurhayati; Rahmania, Sarah; Laily, Dayang; Yulianti, Dian Anggur; Purwati, Nyimas Heny (Jurnal Keperawatan Florence Nightingale, 2024)
This research aims to analyze the application of Kolcaba Model Theory in meeting the needs of comfort in neonates with duodenal atresia. This research is a qualitative research with a case study approach on two neonates treated in the neonatal intensive care unit (NICU). Data were collected through direct observation, in-depth interviews with nurses and parents, and analysis of medical documents of two neonates as samples. The results showed that neonates' physical comfort was partially achieved with stable body temperature, although there were still problems with vital signs and skin condition, which required improvement in pain management and skin care. Environmental comfort was successfully maintained by keeping the baby's body temperature stable, although there were challenges in the room temperature which tended to be cold. These findings emphasize that nursing interventions based on Kolcaba Model Theory need to focus on improving pain management and skin care for physical comfort. The implementation of Kolcaba Model Theory in the care of neonates with duodenal atresia can improve the quality of nursing care in the NICU.